Mass azithromycin for prevention of child mortality among children with acute malnutrition: A subgroup analysis of a cluster randomized controlled trial. - Ali Sié; Mamadou Ouattara; Mamadou Bountogo; Valentin Boudo; Thierry Ouedraogo; Clarisse Dah; Guillaume Compaoré; Elodie Lebas; Huiyu Hu; Travis C Porco; Benjamin F Arnold; Kieran S O'Brien; et al. (Public Library of Science (PLoS), 2024)
Children with acute malnutrition are at high risk of morality. Mass azithromycin distribution reduces all-cause mortality among children aged 1-59 months, and effects may be greater in underweight infants. Here, we evaluate the efficacy of azithromycin for reducing all-cause mortality in children aged 6-59 months with acute malnutrition (mid-upper arm circumference, MUAC, < 12.5 cm). Communities in Nouna District, Burkina Faso were 1:1 randomized to biannual mass distribution of single dose azithromycin or placebo to all children aged 1-59 months. Mortality was assessed during each census and treatment round. MUAC measurements were collected for all children. We evaluated the effect of azithromycin on mortality in subgroups of children aged 6-59 months defined by acute malnutrition (MUAC < 12.5 cm versus MUAC ≥ 12.5 cm). In children with MUAC < 12.5 cm, mortality rates were 51% lower among those living in azithromycin communities compared to placebo (incidence rate ratio 0.49, 95% confidence interval, CI, 0.25 to 0.99; incidence rate difference -18.1 deaths per 1,000 person-years, 95% CI -37.0 to -0.01), which was greater than the reduction in mortality among children with MUAC ≥ 12.5 cm (P-value for interaction on the relative scale = 0.09; P-value for interaction of the additive scale = 0.03). Children with acute malnutrition may benefit from single dose azithromycin above and beyond those without acute malnutrition. Trial registration: ClinicalTrials.gov NCT03676764; https://clinicaltrials.gov/study/NCT03676764.